The Correlation between Students’ Vocabulary Mastery and Their Translation Ability at The First Semester of The Eleventh Grade of Man 2 Bandar Lampung in The Academic Year Of 2017/2018 - Kurniawan, Iwan; Saputri, Anggi Yogi; Isnaini, Rahmiati (Universitas Islam Negeri Raden Intan Lampung, 2021)
In this research, the researcher focused on the correlation between students’ vocabulary mastery and their translation ability. The objective of the research was to know whether there was a correlation between students’ vocabulary mastery and their translation ability at the first semester of eleventh grade of MAN 2 Bandar Lampung in the academic year of 2017/2018. There were two variables in this research, the independent variable, vocabulary mastery (X) and dependent variable, Translation ability (Y). This is correlational research, it is used to know the correlation between vocabulary mastery and translation ability. In taking the sample of the research, the cluster random sampling was applied. The population of the research was taken from the students of eleventh grade of MAN 2 Bandar Lampung in the academic year of 2017/2018. The sample of the research was taken 39 students from 197 populations. In collecting the data of the research, the researcher used objective test that were multiple choices consisted 20 items and one text for translation test. In this research, SPSS was used to compute Pearson Product Moment’s formula.After doing the hypothetical testing, the result demonstrated that there was positive correlation between students’ vocabulary mastery and their translation ability. Based on the data analysis computed by SPSS, it was obtained that Sig (P Value) = 0.000 and α=0.05. It means that Ha was accepted and Ho was rejected because Sig (P Value) =0.000 < α=0.05. Based on this research, it was suggested that to have a good ability in translating, the students should have a good mastery of vocabulary